CONCEPTUAL DESIGN OF AN IMPROVED TRADITIONAL TOFU PRINTING MACHINE - Matzaini, K; Norhanifah, A.R.; Nurul Huda, A. A.; Nurul Azuwa, J.; Rabi’atul Adawiyah, N.; Nursyafiqah, J. (Marine Frontier, 2022)
This study highlights the design process of an improved traditional tofu printing machine. The identified traditional tofu printing machine is currently manually operated, resulting in less efficient energy consumption and quality of tofu production. Therefore, this study aims to help the traditional tofu producer convert the manual process into a semi-automatic tofu printing machine. The design process starts with the need identification, then the creation of Product Design Specification, and lastly, the generation and selection of concepts thru the aid of Morphological and Pugh methods. It was found that the chosen concept was able to press the soymilk efficiently using semi-automatic stamping components. Thus, this helps in saving the human energy usage, cost, and time if using the stamping machine.